Trends And Strategic Issues In Developing Teacher Professionalism In The Era Of Digital Transformation - Fitriana, Heni; Subiyantoro; Silviana, Nur Cholida; Kareng, Muslim (The Faculty of Education and Teaching Training, 2024)
This article examines trends and strategic issues in teacher professional development in the era of digital transformation based on a review of recent literature. The purpose of the study is to identify trends and strategic issues in the development of teacher professionalism in the era of digital transformation through analysis of current literature, in order to formulate policy recommendations that support the improvement of digital competencies, school leadership, and collaboration between stakeholders in education. The research method used is a literature study by analyzing journal articles, books, and research reports related to human resource development in education. The results showed three main trends, namely the utilization of information and communication technology (ICT) in teacher training, the important role of school leadership in supporting teacher professionalism, and strengthening collaboration between schools, universities and the government. Strategic issues identified include the need to improve teachers' digital competencies, strengthening induction programs for novice teachers, and integrated teacher career management. Improving digital competencies is a top priority given that digital transformation has changed the roles and responsibilities of teachers. The implication of this research is the need for adaptive policies in developing teacher professionalism that is responsive to the demands of the digital era.